Ethnicity, race and the prisoner community: shaping meanings in Finnish male prisons - Huhta, Helena (Palgrave Studies in Prisons and Penology, 2024)
This book draws on an in-depth ethnographic study to explore the meanings and consequences of race and ethnicity in daily life within two Finnish male prisons. Set within the context of Finnish immigration, it provides an excellent backdrop for studying social processes in the prison environment launched by a rapid growth in the number of foreign national prisoners. It builds on the sociological attempts to comprehend the nature of the prisoner community from the perspective of ethnicity and race which has gained attention since the 2000s. It explores how ethnic categories are formed in the prison space, prisoner hierarchy and its logics, conflicts and conflict-solving, discrimination and prison officers and development of distinctive prisoner cultures. The study captures the consequences that signifying ethnicity and race have on daily practices, equality, and safety in prison. This book shows how ethnic and racial categories are formed in social action and further, how their meanings are in a constant process of change. Helena Huhta works at the Faculty of Law of the University of Turku, Finland. Before that she was a postdoctoral researcher at the Finnish Youth Research Society.